Como extranjeros entre ciudadanos: multiculturalismo y acatamiento de la soberanía por razón de la residencia - Sauquillo, Julián (Logos. Anales del Seminario de Metafísica, 2002)
Republican and liberal traditions do not encourage a framework of understanding between different cultures. An ethical and political design of a plural society must be created whereby the maze of cultures we live among may be accommodated for. The most dominant moral conceptions in this sense are relativism, universalism and fundamentalism. All of these positions have different limitations and possibilities. The author chooses to defend a “modus vivendi” among cultures which does not bring forth indifference or contempt to others, namely foreigners– immigrants or refugees. The “modus vivendi” defended must transcend simple coexistence among cultures and adopt a cosmopolitan view, calling for sacrifices in solidarity with those who do not share our culture. This open way of living can lead to real dialogue among cultures, starting with the acknowledgement of their diversities, which are neither homological nor can they be placed in order of priority from the “western ethnocentric” point of view.